Development of a Propensity to Self-Medicate with Over-the-Counter Medicines Scale (PSM-OTC) - Oluwasola Ayosanmi; Marjorie Delbaere; Jeff Taylor (University of Minnesota Libraries Publishing, 2022)
Objective: To develop a valid and reliable scale to measure the public's propensity to self-medicate with OTC medicines. Method: Propensity construct items were obtained from the literature and also created as new entities. Three experts reviewed the item pool for face validity. Internal consistency was assessed using Cronbach's alpha. Test-retest reliability was estimated using Pearson correlation coefficients (r), Intraclass Correlation Coefficients (ICC) and paired sample t-tests. Further test-retest reliability assessed the degree of change in responses in a subset of subjects from time 1 to time 2 (one month apart) for each item on the scale. Results: From the pool, 16 items were assessed for applicability to the propensity construct. Factor Analysis identified four components and were labelled as purchase involvement, self-efficacy, awareness of care needed during self-medication, and the therapeutic usefulness of OTC medicines. The internal consistency of the 16-item scale was sufficient; overall alpha was 0.9 and each construct had an alpha of 0.7 to 0.8. Test-retest reliability coefficients (r) for the four components were reassuring, ranging from 0.4 to 0.5, while the ICC values ranged from 0.5 to 0.7. A paired sample t-test showed no statistically significant difference in the rating at the two iterations for each of the constructs, thereby suggesting good reliability of the data. Over 50% of respondents did not change their original response to the 7-point scales (strongly disagree (1) to strongly agree (7)) for 9 out of 16 items. Factor loading from Principal Component Analysis led to the reduction of the 16-items scale to a 15-item Propensity to Self-Medicate with OTC Medicines Scale. Conclusion: The developed tool for measuring the propensity to self-medicate with OTC medicines showed acceptable performance of internal consistency and reliability. The scale may have research potential in assessing the self-medication propensity of different cohorts of society.